Disease-Modifying Therapy (DMT) Switch in Highly Active Multiple Sclerosis: A Case Report - Rocksy Fransisca V Situmeang; Nadia Gabriella (MEDICINUS, 2025)
Background: Highly active multiple sclerosis (HAMS) is a severe phenotype of multiple sclerosis (MS), accounting for 10% of all relapsing-remitting MS (RRMS) cases, characterized by rapid clinical decline and disease progression despite treatment with disease-modifying therapy (DMT). It is associated with high morbidity and mortality rates, thus requiring different therapeutic approaches. We report a case of DMT switch in a 30-year-old female with HAMS. Case: A 30-year-old female presented with a 3-month history of numbness and tingling on her fingers, back, and lower extremities. Examination revealed hyperreflexia and positive Hoffman-Tromner sign. Brain magnetic resonance imaging (MRI) revealed multiple demyelinating lesions suggestive of MS, including Dawson’s fingers. She was diagnosed with MS and initially treated with subcutaneous (SC) interferon beta-1a (IFNβ-1a) 22 mcg, three times weekly. As the patient continued to experience relapses and develop new lesions on biannual repetition of scans, she was diagnosed with RRMS. Four years after the initial diagnosis, her relapses became more frequent with incomplete recovery in between, suggestive of HAMS. Therapy was subsequently switched from IFNβ-1a to cladribine. Conclusion: Two approaches in the treatment of MS are the escalation and induction therapy. To date, no standardized treatment protocols for HAMS have been established. Patients with HAMS are candidates for the induction approach due to the narrow window of opportunity for treatment and the risk of early disease progression. Despite the risk of developing adverse reactions from being on potent immunosuppressive drugs, the imminent neurological disability that comes with HAMS outweighs this risk. The use of immune-reconstitution DMTs helps to achieve no evidence of disease activity (NEDA). Cladribine has shown promising outcomes in the treatment of HAMS and is frequently used for induction therapy.